PUSAT KREATIVITAS REMAJA DAN ANAK MUDA MILENIAL - Stefanus Sutanto; Dewi Ratnaningrum (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
In this modern age we often hear the term Millennial, Millennial is a young person today who was born between 1980-2000an. Especially in Indonesia even Millennials are very numerous, millennials are young people who certainly have many abilities and diverse creativity which of course can be developed in a positive way for the ability in each of them. Activities that can build their creativity are certainly very pleasant besides being able to fill their time with useful things besides that they can also increase their ability for the future so they can have an entrepreneurial spirit. This project aims to accommodate millennials who can develop their abilities and the creativity they have to develop in the future so that they can have an entrepreneurial spirit besides being able to fill time with useful and positive things and socializing to meet many people who have a passion and the same creativity so that it can add insight. This project is a place that accommodates teenagers and millennial young people to develop their talents and creativity in the activities they enjoy. as well as being a new non-formal teaching place for the Tangerang city, specifically Alam Sutera. The method used is descriptive where direct observation is carried out in the field and analysis of data - data to determine the space requirements to obtain the relationship of space and circulation in the site. From the results that have been found, a round / curved form of building mass is formed, with a façade that tends to be modern, depicting young people who are dynamic and not fixated in monotone activities. Activity groups are based on zoning and pay attention to the privacy of each activity and each activity can be obtained from the results of a survey with most young people and adolescents living in the Alam Sutera area. AbstrakPada zaman modern ini kita sering mendengar istilah Milenial, Milenial adalah anak muda pada sekarang ini yang lahir di antara tahun 1980-2000an. Terutama di Indonesia pun kaum Milenial sangatlah banyak, kaum milenial pun adalah kaum muda yang pastinya memiliki banyak kemampuan dan kreativitas yang beragam yang tentunya dapat di kembangkan dalam hal yang positif untuk kemampun dalam diri mereka masing-masing. Kegiatan yang dapat membangun kreativitas mereka tentunya sangat menyenangkan selain dapat mengisi waktu dengan hal yang berguna selain itu pun  juga bisa menambah kemampuan diri untuk masa depan agar bisa memiliki jiwa entrepreneur. Proyek ini memiliki tujuan untuk mewadahi para kaum milenial bisa mengembangkan kemampuan mereka serta kreativitas yang mereka miliki untuk di kembangkan untuk kedepannya agar bisa mempunyai jiwa entrepreneur selain itu juga dapat mengisi waktu dengan hal yang berguna dan positif serta bersosialiasi bertemu dengan orang banyak yang memiliki kegemaran dan kreativitas yang sama sehingga dapat  menambah wawasan. Proyek ini adalah tempat yang mewadahi para remaja dan anak muda milenial untuk mengembangkan bakat dan kreativitas mereka dalam kegiatan yang mereka gemari. sekaligus menjadi tempat pengajaran non formal baru bagi kota Tangerang khusus nya Alam Sutera. Metode yang digunakan adalah deksriptif di mana dilakukan pengamatan langsung di lapangan dan analisis data – data untuk menentukan kebutuhan ruang hingga didapatkan hubungan ruang serta sirkulasi di dalam tapak. Dari hasil yang sudah di dapati, terbentuklah bentuk massa bangunan yang bundar/melengkung, dengan façade yang cenderung modern, Menggambarkan anak muda yang dinamis dan tidak terpaku dalam kegiatan yang monotone saja. Kelompok kegiatan dibuat berdasarkan zoning dan memperhatikan privasi dari tiap kegiatan serta setiap kegiatan di dapat dari hasil survey dengan sebagian besar anak muda dan remaja yang tinggal di kawasan Alam Sutera.